Pengaruh Sharia Governance, Good Corporate Governance, Dan Dewan Pengawas Syariah Terhadap Pencegahan Fraud Pada Bank Umum Syariah Di Indonesia Periode 2019-2024 - Iviola Sabila Avandi; Anggun Okta Fitri; Muhammad Iqbal (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
This study aims to analyze the influence of Sharia Governance, Good Corporate Governance (GCG), and the Sharia Supervisory Board (DPS) on fraud prevention in Sharia Commercial Banks in Indonesia during the 2019–2024 period. Even though governance implementation in Islamic banking continues to be strengthened, fraud cases still occur, so the effectiveness of Sharia supervisory mechanisms needs further examination. Moreover, previous research results still show inconsistent findings and generally have not tested these three variables simultaneously in Sharia Commercial Banks. This study uses a quantitative approach with a causal associative research type and utilizes secondary data sourced from annual reports, Good Corporate Governance reports, Sharia Governance reports, and Sharia Supervisory Board reports. The sample is determined using a purposive sampling technique, resulting in 12 Sharia Commercial Banks with 72 observations over six years. The analysis was conducted using panel data regression with a Fixed Effect Model (FEM) approach. The study results show that Sharia Governance has a positive and significant effect on fraud prevention. Meanwhile, Good Corporate Governance and the Sharia Supervisory Board show a positive influence, but they do not have a significant partial effect yet. Simultaneously, all three variables have a positive and significant effect on fraud prevention. This study contributes to enriching the literature on the effectiveness of Sharia governance by testing the integrated mechanism of three oversight systems in Sharia Commercial Banks in Indonesia. The findings suggest the importance of strengthening Sharia-based and spiritual governance oversight systems by the Financial Services Authority (OJK) and Sharia Commercial Banks to enhance fraud prevention effectiveness and maintain public trust.